Scientific Argumentation Measurement Pattern of Pre-Service Elementary School Teachers: A Literature Review - Fina Fakhriyah; Ani Rusilowati; Sunyoto Eko Nugroho; Sigit Saptono (Universitas Negeri Semarang, 2022)
Abstrak. Scientific argumentation is a means to encourage students' critical thinking skills toward natural phenomena. By having scientific argumentation, a higher conceptual understanding of students could be ensured. This research aims to review and explore the related scientific argumentation findings for describing the importance of scientific argumentation measurement and finding out the patterns of scientific argumentation measurement. The literature review analyses showed that scientific argumentation-based learning could improve critical thinking, creative thinking, and problem-solving skills. Besides that, the scientific argumentation measurement pattern could be found out by using Toulmin Argumentation Pattern (TPA), Scientific Argumentation and Reasoning (SRA), and Claim, Evidence, and Reasoning (CER). Scientific argumentation could be used to improve students' understanding of scientific concepts related to science phenomena. Thus, creating conclusions and understanding learning concepts by using claims and rebuts logically, analytically, and scientifically could occur. The empowerment strategy by using scientific argumentation measurement pattern is important to apply. Using an appropriate learning model is also important to create better students' outcomes with 21st-century skills.Key words: scientific arguments, measurement pattern, literature review